LEO mega-constellation network:networking technologies and state of the art - Quan CHEN; Lei YANG; Jianming GUO; Xingchen LI; Yong ZHAO; Xiaoqian CHEN (Tongxin xuebao)
The emerging low earth orbit (LEO) mega-constellation network (MCN) represented by Starlink and OneWeb were studied.The system architecture and basic working modes were introduced, and the main features of the emerging broadband MCN were summarized.Based on the system architecture of MCN, the methodology and research progress of five key technologies were investigated and summarized, including network topology dynamics management, space-ground handover scheme, high-efficiency routing algorithm design, gateway placement design, network simulation and performance evaluation.The focus was on recent mega-constellation-related studies.The challenges caused by the large scale and complexity of MCN and the applicability of existing techniques and solutions in MCN were analyzed.